Evaluation of the global impacts of mitigation on persistent, bioaccumulative and toxic pollutants in marine fish - Bonito,Lindsay T.; Hamdoun,Amro; Sandin,Stuart A. (PeerJ, 2016)
Although persistent, bioaccumulative and toxic pollutants (PBTs) are well-studied individually, their distribution and variability on a global scale are largely unknown, particularly in marine fish. Using 2,662 measurements collected from peer-reviewed literature spanning 1969–2012, we examined variability of five classes of PBTs, considering effects of geography, habitat, and trophic level on observed concentrations. While we see large-scale spatial patterning in some PBTs (chlordanes, polychlorinated biphenyls), habitat type and trophic level did not contribute to significant patterning, with the exception of mercury. We further examined patterns of change in PBT concentration as a function of sampling year. All PBTs showed significant declines in concentration levels through time, ranging from 15–30% reduction per decade across PBT groups. Despite consistent evidence of reductions, variation in pollutant concentration remains high, indicating ongoing consumer risk of exposure to fish with pollutant levels exceeding EPA screening values. The temporal trends indicate that mitigation programs are effective, but that global levels decline slowly. In order for monitoring efforts to provide more targeted assessments of risk to PBT exposure, these data highlight an urgent need for improved replication and standardization of pollutant monitoring protocols for marine finfish.
Keywords: Contaminants; Marine fish; Muscle tissue; Seafood; Persistent organic pollutants; Global; Toxins